Mobile cloud computing for emergency healthcare model:framework - Nirabi, Ali; Hameed, Shihab Ahmed (Institute of Electrical and Electronics Engineers Inc., 2018)
There has been recently acceptance of traditional emergency, although there are weaknesses like an wasting time for serving emergency cases and this may threaten a patient’s life, information and communication technologies (ICT) have become more important in human life after its development for more than half a century with the great advantages of computing system like scalability of resources and reliability it is avoiding the system being a down if the server had issues or any bug, this paper will present Mobile cloud computing for emergency health care model (MCCEH) model using a cloud computing server, MCCEH model providing services related to healthcare in emergency cases and aim to reduce response time to save the patient's life. When a person is exposed to a health problem or a traffic accident is occurs, MCCEH model will allow users to search for the nearest medical center or nearest specialists related to specific specialization and the results will show the availability timetable for every specialist and whether he is available at this time or not, the user will be able to choose specialist / medical center based on previous experiences may able to read previous feedback and opinions.